1994
DOI: 10.1677/joe.0.1410109
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ovulation by endothelin-3 in rats

Abstract: Endothelins vary in their biological activity. We therefore examined the effects of endothelin-3 (ET-3) on ovulation and secretion of LH, FSH and prolactin in rats in which naturally occurring ovulation was blocked by the administration of sodium pentobarbital (40 mg/kg, i.p.) prior to the critical period (1330 h) on the day of pro-oestrus. ET-3 (10 nmol/kg) was given via the jugular vein under pentobarbital anaesthesia from 1600 to 1800 h on the day of pro-oestrous and induced ovulation in all rats whether gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…in rats, whereas in another study, i.v. application of ET-3 in rats induced a more prominent release of LH in comparison to FSH and, moreover, initiated ovulation (Furudate et al, 1994). Furthermore, in the latter study a biphasic PRL response similar to in vitro findings was observed.…”
Section: Experiments In Animalssupporting
confidence: 82%
“…in rats, whereas in another study, i.v. application of ET-3 in rats induced a more prominent release of LH in comparison to FSH and, moreover, initiated ovulation (Furudate et al, 1994). Furthermore, in the latter study a biphasic PRL response similar to in vitro findings was observed.…”
Section: Experiments In Animalssupporting
confidence: 82%
“…There are several lines of evidence that point to endothelins participating in the regulation of pituitary hormone secretion (Vierhapper et al ., 1993; Vierhapper, 1996; Kiefer et al ., 2000). Release of LH and FSH is stimulated by ET‐3 (Kanyicska et al ., 1991; Furudate et al ., 1994; Naruse et al ., 1994). It was recently demonstrated that human neurons secreting GnRH produce and respond to ET‐1 and that this peptide positively regulates GnRH secretion (Maggi et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of TSH were measured by radioimmunoassay (RIA), previously reported method (Furudate et al, 1994), using reagents provided by the Rat Pituitary Hormone Program, NIDDK, NIH. The second antibody was anti‐rabbit IgG goat serum (donated by Dr. K. Wakabayashi).…”
Section: Methodsmentioning
confidence: 99%